Networking and Libraries - Juneja, P. K. (Journal of Information and Knowledge, 1987)
This paper describes the development of networking in India with special emphasis on Project INDONET, India’s First National Computer Network. The primary objective of project INDONET is the establishment of a network of computing centres accessible from remote parts of the country so as to deliver the benefits of information resources management to a wider section of users in the country. This will enable, among others, the predominantly large primary sector as well as industrial and service organisations in remote areas to have access to effective and modern information techniques. This approach would, provide an optimal solution to the long term requirements of modern and sophisticated computing equipment in the country. This paper also deals with the Electronic Mail System to be provided on INDONET. These efforts will lead to a flexible and reliable modern computer network offering users many services covering requirements foreseen for a long period of time and offering libraries a network that is easy to operate, expand and maintain.